Semiparametric Exploration of Long Memory in Stock Prices - LEE, David K. C. (Institutional Knowledge at Singapore Management University, 1996)
New or modified methods for semiparametric analysis of fractional long memory in time series are described and applied to twenty-six stock prices and two stock indices. Evidence is found that some, but not all, of the stocks have long memory, while one of the indices exhibits mean reversion.